2015
DOI: 10.1007/s11099-015-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between potassium uptake and salt tolerance in wheat

Abstract: The aim of our study was to answer whether any positive correlation exists between K + uptake and salt tolerance in wheat. We carried out a sand-culture experiment with salt-tolerant, DK961 (ST), and salt-sensitive, JN17 (SS), wheat cultivars, where photosynthesis, the K + /Na + ratio, growth, and the biomass yield were examined. The seeds were exposed for four weeks to six NaCl concentrations (50, 100, 150, 200, 250, and 300 mM), which were embodied in the Hoagland solution. Salinity-induced decrease of K + o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It has been shown that the phenotypic appearance of the wheat seedlings grown under salinity stress conditions correlate well with their biochemical properties [such as the content of ascorbic acid, H 2 O 2 , MDA (TBARS in our case) and reduced glutathione, (Hasanuzzaman et al, 2011 )]. Several other works also reported that there is a positive correlation between chlorophyll content, the activity of antioxidant defense system and the salt stress tolerance of various wheat cultivars (e.g., Cheng et al, 2015 ; Bharti et al, 2016 ; Jan et al, 2017 ; Kumar et al, 2017 ).…”
Section: Resultsmentioning
confidence: 89%
“…It has been shown that the phenotypic appearance of the wheat seedlings grown under salinity stress conditions correlate well with their biochemical properties [such as the content of ascorbic acid, H 2 O 2 , MDA (TBARS in our case) and reduced glutathione, (Hasanuzzaman et al, 2011 )]. Several other works also reported that there is a positive correlation between chlorophyll content, the activity of antioxidant defense system and the salt stress tolerance of various wheat cultivars (e.g., Cheng et al, 2015 ; Bharti et al, 2016 ; Jan et al, 2017 ; Kumar et al, 2017 ).…”
Section: Resultsmentioning
confidence: 89%
“…Grass pea seedlings under 50 mM NaCl, despite increasing content of Na + ions, retained the ability to grow and develop, which may indicate effective Na + sequestration in the vacuoles. Additional to Na + sequestration, plants can endure ion toxicity by taking up and accumulating potassium [ 57 ]. A higher K + ion uptake was observed in salinity tolerant plants than in salinity sensitive plants [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress causes significant decreases in the growth and productivity of crops, but the application of potassium was found to improve the growth and biomass yield of bean under salt stress (Dawood et al 2014). Cheng et al (2015) found that plant salt tolerance might be positively correlated with plant abilities for K + transport and retention, higher K + affinity may be a key factor for better PNmax/biomass yields of wheat under salt stress. Also, Chakraborty et al (2016) reported that potassium had a significant effect on salt tolerance in peanut, which was reflected in reduced Na + uptake achieved by adjusting the tissue ionic balance and improving biomass production.…”
Section: Introductionmentioning
confidence: 99%